Oral efficacy of a leukotriene B4 receptor antagonist in colitic cotton-top tamarins. Issue 5 (November 1995) - Fretland, D; Sanderson, T; Smith, P; Adams, L; Carson, R; Fuhr, J; Tanner, J; Clapp, N
Abstract : Leukotriene B4 (LTB4) is a potent neutrophil activator and chemotaxin that is present in increased concentrations in the colonic tissue and rectal dialysates of acute ulcerative colitis patients. Cotton-top tamarins (CTTs) with confirmed active colitis were treated with the second generation LTB4 receptor antagonist, SC-53228 ((+)-(S)-7-[3-(2-cyclopropyl-methyl)-3-methoxy-4-[(methylamino) carbonyl]phenoxy]propoxy]-3, 4-dihydro-8-propyl-2H-1-benzopyran-2- propanoic acid), 20 mg/kg bodyweight by gavage, twice daily for 56 days. End points were body weights, stool consistency, colonic endoscopy, assay of inflammatory mediators, and haematology and clinical chemistry tests. LTB4 and prostaglandin E (PGE) values were measured in rectal dialysates at pretreatment, 28 day and 56 day time points. LTB4 concentrations were reduced from pretreatment mean (SEM) values of 37.3 (0.8) ng/ml to 3.7 (0.8) ng/ml (p < 0.001) and 2.3 (0.5) ng/ml (p < 0.01) at days 28 and 56, respectively. On the other hand, mucosal protective PGE values remained constant or slightly increased during SC-53228 treatment (pre: 6.9 (2.2) ng/ml; day 28: 6.7 (1.4) ng/ml; day 56: 9.9 (1.6) ng/ml). Furthermore, assessment of a panel of 35 clinical chemistry and haematology parameters throughout the treatment showed there were no significant untoward effects of drug treatment. Six CCTs finished the eight week treatment and five of six gained weight (ranging from 27-121 grams each) while one CTT lost weight (50 g). Stool condition improved in five of six animals while one of six remained unchanged. All CCTs showed dramatic improvement histologically, with no or only minimally active colitis after treatment. The histological changes plus significant weight gains and improvement of stool condition (quality of life parameters) after eight weeks of SC-53228 treatment were remarkable. Furthermore, in follow up biopsies seven months after treatment ceased, three of six CTTs had no active colitis. This is the first time afflicted CTTs have not had recurring colitic exacerbations after a treatment regimen was stopped. It is concluded that in colitic CTTs, SC-53228 has shown both an immediate and a long acting anticolitic activity. It is also concluded that reduced LTB4 concentrations during treatment inhibited neutrophil infiltration of the colonic tissue and this, coupled with the maintenance of mucosal protective prostaglandins, contributed to the dramatic anticolitic efficacy. The treatment was safe over eight weeks. A compound such as SC-53228 may be useful in the medical treatment of human inflammatory bowel disease.